Propriedades estruturais e ópticas de células solares InGaP/GaAs - Corrêa, Mozart de Ávila (Universidade Federal de São Carlos, 2025)
The growing demand for renewable energy sources has driven the development of high-efficiency solar cells. Multijunction (or tandem) solar cells, composed of semiconductors with different bandgaps, allow for better utilization of the solar spectrum and have already demonstrated efficiencies exceeding 40%. However, further advances are still needed to optimize crystal quality and reduce optical and electronic losses in these devices. This work investigates the effect of GaAs substrate orientation and doping on optically active defects in p-(i/n)-n GaAs/In₀.₄₈Ga₀.₅₂P/GaAs solar cell heterostructures grown by metalorganic chemical vapor deposition (MOCVD). Photoluminescence (PL) spectroscopy revealed different emission bands, associated with excitonic transitions and free carriers in disordered regions of InGaP. In addition, spatially indirect transitions were identified in ordered domains, involving electrons in donors and photoexcited holes. Furthermore, the PL spectra were also influenced by different degrees of atomic ordering among the samples, with an increase in ordered domains observed for the misoriented substrate compared to the doped exact (100) orientation, while n-type doping resulted in reduced ordering relative to the undoped exact (100) sample. These findings contribute to a better understanding of the relationship between crystal structure and the optical properties of InGaP, supporting the optimization of high-efficiency photovoltaic devices.
Structural and Optical Properties of InGaP/GaAs Solar Cells
Keywords: InGaP; Orientação do substrato; Defeitos; Características elétricas; Fotoluminescência; ENGENHARIAS::ENGENHARIA ELETRICA::MATERIAIS ELETRICOS